Multi-Scale Assessment of GPM Satellite Precipitation Products in Weihe River Basin - GUO Binbin; DAI Zhong (Renmin Zhujiang)
To explore the accuracy and applicability of near real-time (IMERG-Early, IMERG-Late and GSMaP-NRT) and post-real-time (IMERG-Final, GSMaP-Gauge and GSMaP-MVK) remote sensing precipitation products from the global precipitation measurement (GPM) program in complex terrain basins, this study conducted a comprehensive assessment on the accuracy evaluation indexes (CC, RMSE and BIAS) and precipitation capacity detection indexes (POD, FAR and CSI) of remote sensing precipitation based on rain gauge data in the Weihe River Basin across various spatial and temporal scales. Additionally, the IHACRES hydrological model was employed to assess the applicability of satellite precipitation data in runoff simulation. The results show that both GSMaP-Gauge (CC = 0.55, RMSE = 5.09 and Bias = 0.3%) and IMERG-Final (CC = 0.458, RMSE = 5.92 and Bias = 8%) precipitation products accurately reflect the spatiotemporal distribution characteristics of precipitation but generally tend to overestimate the precipitation. The data of precipitation products in GSMaP and IMERG series exhibits significantly obviously lower precipitation detection capabilities in winter (POD < 0.4) than in other seasons. The satellite precipitation data is significantly affected by altitude, and its quality declines with increasing altitude. The IHACRES model driven by IMERG-Final performs the best (NSE = 0.856), with monthly Nash efficiency coefficients greater than 0.8 for hydrological models driven by GSMaP-Gauge and IMERG-Final, suggesting that these data can be used as precipitation inputs for regional hydrological process simulation.